1980
DOI: 10.1111/j.1365-2125.1980.tb04925.x
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of guanfacine and clonidine during wakefulness and sleep in healthy subjects.

Abstract: 1 Three double-blind studies in young normotensive male volunteers were carried out: a study in ten awake subjects, comparing guanfacine 2.0 and 4.0 mg with clonidine 0.15 and 0.30 mg and placebo; and two polygraphic sleep studies each with six subjects, comparing guanfacine 1.0 and 2.0 mg with-placebo, and clonidine 0.15 and 0.30 mg with placebo, respectively. 2 In awake subjects, both drugs reduced systolic blood pressure without significantly altering diastolic blood pressure, pulse rate and objective perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…Even so, medications can complicate the clinical picture, since psychostimulants can increase sleep-onset latency (Weiss & Salpekar, 2010). Conversely, α 2 -adrenoceptor agonists have been used to facilitate sleep, although there are limited data regarding their impact on sleep parameters (Spiegel & DeVos, 1980; Weiss & Salpekar, 2010), and even afternoon doses of traditional stimulants may sometimes improve sleep in children with ADHD (see discussion in Spruyt & Gozal, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Even so, medications can complicate the clinical picture, since psychostimulants can increase sleep-onset latency (Weiss & Salpekar, 2010). Conversely, α 2 -adrenoceptor agonists have been used to facilitate sleep, although there are limited data regarding their impact on sleep parameters (Spiegel & DeVos, 1980; Weiss & Salpekar, 2010), and even afternoon doses of traditional stimulants may sometimes improve sleep in children with ADHD (see discussion in Spruyt & Gozal, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…That lofexidine targets imidazoline receptors and decreases presynaptic noradrenergic release and subsequent sympathetic drive may account for the prominence of this AE in the present study. A more specific α-2 adrenergic receptor agonist, such as guanfacine, may be worth evaluating since it is less sedating, better tolerated, has a longer half-life, and has more selectivity for α-2 adrenergic receptors found in prefrontal cortex (Nami et al 1983; Ramos et al 2006; Spiegel & DeVos 1980). Of particular interest, a recent study in 20 cocaine-dependent individuals showed that guanfacine lowered stress- and cue-induced nicotine craving and cue-induced cocaine craving, anxiety and arousal (Fox et al 2012); suggesting that guanfacine warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…CNS-depressant effect. This also suggests the possibility of an effect on waking and sleeping cycle [33]. According to a classification of the typical waking EEG profiles of psychotropic drugs in healthy volun teers [10], they would be classified as sedative drugs.…”
Section: Discussionmentioning
confidence: 99%